A review on medicinal plants of ParkiaBiglobosa (Mimosaceae -Fabaceae) and PterocarpusErinaceus (Leguminosae – Papilionoidea) - Adenile, Dourossimi Adam (My University, 2016)
The use of the medicinal plants constitutes a significant resource employed by communities for their daily healthcare. Parkia biglobosa and Pterocarpus erinaceus are two plants spread in West Africa and used in traditional medicine. This study was carried out in order to summarize current knowledge on medicinal uses of these plants. Data from this study showed that the plants possessed wide-reaching pharmacological actions, including anti - diarrhoea, antimicrobial, antihypertensive, anti-inflammatory, analgesic, antiplasmodial activity. All the parts of the plants are used for the care. Phytochemical investigations revealed that some compounds as alkaloids, tannins, saponins, flavonoids, steroids, phenols, glycoside and sugars are present.
Keywords: Parkia biglobosa; Pterocarpus erinaceus; ethnopharmacological; traditional medicine